(untitled) (Bangladesh Journal of Medicine, 2021)
Objectives: To observe the organic change occurs in dyspeptic patient by upper gastrointestinal endoscopy. Methods: The present prospective, observational, cross-sectional study was conducted at Medicine and Gastroenterology department of Sir Salimullah Medical College & Mitford Hospital, over a period of 6 month from 2019 to 2020.The study population was 200with aged18 years and above, irrespective of sex and who were suffering from dyspeptic symptoms for at least 6 months duration. Data regarding the demographic profile of study population nand endoscopic findings were processed and analyzed using software SPSS (Statistical Package for social science) version 26. Results: It was observed that most of the dyspeptic patients 71%were showing normal endoscopic findings and 29% have abnormal endoscopy findingwhere majority of the patient were 51 – 70 years of age.Out of them 41% of male and 26% of female had organic changes. It was also found that 46% of the patients were smoker and among them 34(37%) had abnormal endoscopic finding where 24(22%) non-smokerpatient had abnormal finding, which were statistically significant (p,0.05) between two group. Among abnormal endoscopic finding, 11% gastric erosions, 08% gastric ulcer, 04% duodenal erosions, 03% duodenal ulcer, 02% reflux oesophagitis, and carcinoma stomach rare 01%. Conclusion: The study concludes that majority of patients with complaints of dyspepsia have no organic lesion and can be considered non ulcer dyspepsia. The common abnormal endoscopic findings included gastric erosion and gastric ulcers relating to dyspepsia. The study findings also suggest that smoking is a risk factor for developing organic changes in dyspeptic patients specially in middle age group. Bangladesh J Medicine July 2022; 33(1) : 3-7